Silymarin Enriched Extract (Silybum marianum) Additive Effect on Doxorubicin-Mediated Cytotoxicity in PC-3 Prostate Cancer Cells - Gioti, Katerina; Papachristodoulou, Anastasia; Benaki, Dimitra; Havaki, Sophia; Beloukas, Apostolos; Vontzalidou, Argyro; Aligiannis, Nektarios; Skaltsounis, Alexios-Leandros; Mikros, Emmanuel; Tenta, Roxane (Planta Medica, 2019)
Silymarin-enriched extract (SEE) is obtained from Silybum marianum (Asteraceae). Doxorubicin (DXR) is a widely used chemotherapeutical yet with severe side effects. The goal of the present study was to assess the pharmacologic effect of SEE and its bioactive components silibinin and silychristine when administrated alone or in combination with DXR in the human prostate cancer cells (PC-3). PC-3 cells were treated with SEE, silibinin (silybins A and B), silychristine, alone, and in combination with DXR, and cell proliferation was assessed by the MTT assay. Cell cycle, apoptosis, and autophagy rate were assessed by flow cytometry. Expression levels of autophagy-related genes were quantified by qRT-PCR, ELISA and western blot while transmission electron microscopy was performed to reveal autophagic structures. Finally, NMR spectrometry was used to identify specific metabolites related to autophagy. SEE inhibited PC-3 cell proliferation in a dose-dependent manner while the co-treatment (DXR-SEE) revealed an additive cytotoxic effect. Cell cycle, apoptosis, and autophagy variations were observed in addition to altered expression levels of autophagy related genes (LC3, p62, NBR1, Beclin1, ULK1, AMBRA1), while several modifications in autophagic structures were identified after DXR-SEE co-treatment. Furthermore, treated cells showed a different metabolic profile, with significant alterations in autophagy-related metabolites such as branched-chain amino acids. In conclusion, the DXR-SEE co-treatment provokes perturbations in the autophagic mechanism of prostate cancer cells (PC-3) compared to DXR treatment alone, causing an excessive cell death. These findings propose the putative use of SEE as an adjuvant cytotoxic agent.
Keywords: Silybum marianum; Asteraceae; silymarin; doxorubicin; prostate cancer; autophagy